Single pass fiber laser butt welding of explosively welded 2205/X65 bimetallic sheets and study on the properties of the welded joint - Gou, Ning-Nian; Zhang, Jian-Xun; Zhang, Lin-Jie; Li, Zhen-Gang; Bi, Zong-Yue (International journal of advanced manufacturing technology, 2016)
In this study, the explosively welded 2205 duplex stainless steel/X65 pipe steel bimetallic sheets were butt welded by a fiber laser in single pass. The microstructure, mechanical, and corrosion properties of the laser butt welded (LBW) joint were investigated. The results show that the upper fusion zone (FZ) is composed of the martensite and bainite phases, while the lower FZ is composed of austenite (A) and ferrite (F). Energy dispersive spectroscopy (EDS) test results indicate that only a small amount of Cr, Ni, and Mo migrated from the lower FZ to the upper FZ, whereas a small amount of Fe has been moved from the upper FZ to the lower FZ. During the tensile test process, The digital specklegram processing technology test results demonstrated that the fracturing of the specimens started at the lower FZ, and then the fracture grew towards the parent plates near the upper FZ. The face and root bend tests were carried out, and no separation, tearing, or fracture was observed around the joint. Accelerated corrosion test results show that the LBW joint has the superior corrosion resistance, but it has poor pitting corrosion resistance.